2016
DOI: 10.1136/openhrt-2016-000501
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the long-term care insurance certificate for predicting 1-year all-cause readmission compared with validated risk scores in elderly patients with heart failure

Abstract: ObjectivesReadmission is a common and serious problem associated with heart failure (HF). Unfortunately, conventional risk models have limited predictive value for predicting readmission. The recipients of long-term care insurance (LTCI) are frail and have mental and physical impairments. We hypothesised that adjustment of the conventional risk score with an LTCI certificate enables a more accurate appreciation of readmission for HF.MethodsWe investigated 452 patients with HF who were followed up for 1 year to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Most patients with HF have to live in their houses after discharge and manage daily living with HF by themselves or have family support. A single‐center study from Ozu City showed that 37% of patients had LTCI 21 . This percentage was also two times higher than those of community‐dwelling people in Japan, which might indicate that patients with HF had a two times higher risk of burden for the LTCI.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients with HF have to live in their houses after discharge and manage daily living with HF by themselves or have family support. A single‐center study from Ozu City showed that 37% of patients had LTCI 21 . This percentage was also two times higher than those of community‐dwelling people in Japan, which might indicate that patients with HF had a two times higher risk of burden for the LTCI.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown some predictors of functional decline after HF [ 7 , 20 22 , 24 ]. While those studies examined risk factors for functional disability, their timing of assessment differed from our study, that is, while previous studies were conducted on hospital admission and/or at discharge, we gathered information on risk factors in subjects initially free of diseases and identified etiologic precursors by following up for 11 years.…”
Section: Discussionmentioning
confidence: 99%
“…Existing research has assessed socioeconomic status and cardiovascular risk factors at the time of hospital admission for HF. In particular, studies have focused on cardiac function after HF, for example, ejection fraction and valvular diseases [ 24 , 29 ]. In the present study, we assessed baseline risk factors obtained several years before HF onset.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This poses significant problems, including prognosis, impaired quality of life and increased costs and resource use 1–4. Also, ageing patients with HF are increasingly common in an ultra-ageing society, and the majority of them are frail and suffer from multiple chronic comorbidities 5–10. These patients require readmissions due to worsening HF and other comorbidities 2…”
Section: Introductionmentioning
confidence: 99%